Hepatitis C virus infection and the risk of Sjögren or sicca syndrome: a meta‐analysis. (December 2014) - Wang, Yan; Dou, Hengli; Liu, Guowei; Yu, Lili; Chen, Shimin; Min, Yan; Zhao, Kanghai; Wang, Xingjuan; Hu, Chengjin
Abstract Previous studies have suggested an association between hepatitis C virus (HCV) infection and the development of Sjögren's syndrome (SS), also known as sicca syndrome. The main objective of this study was to summarize the existing evidence and quantitatively evaluate the association between hepatitis C virus infection and SS/sicca syndrome by performing a meta‐analysis of observational studies. MEDLINE and PubMed (January 1980–August 2013) were searched to identify relevant studies in English. Outcomes were calculated and are reported as odds risk (OR) and 95% CIs based on a random‐effects model. Heterogeneity was assessed with I2 statistics. Quality assessment was performed with the Newcastle–Ottawa scale. Based on meta‐analysis of five cross‐sectional and five cohort studies, a significant positive relationship between HCV infection and development of SS/sicca syndrome was found, the pooled random effects OR being 3.31 (95% CI, 1.46–7.48; P < 0.001). In subset analyses, the studies that used European diagnostic criteria showed a higher summary OR than did studies that adopted other diagnostic criteria. When the data were stratified by source of controls, significant associations were also observed when healthy people (OR = 9.44; 95% CI = 2.67–33.40; P = 0.204) or subjects with hepatitis B virus infection (OR = 6.57; 95% CI = 1.21–35.57; P = 0.5) were used as controls, but not when the controls were hospital‐based (OR = 0.99; 95% CI = 0.61–1.61; P = 0.169). In summary, the findings suggest that HCV infection is associated with SS/sicca syndrome. The observed increased risk in studies in which European diagnostic criteria and healthy controls were used and the decreased risk in studies with hospital‐based controls may be attributable to selection bias or other unknown factors.